Alkalinity in Tidal Tributaries of the Chesapeake Bay. Issue 1 (9th January 2020) - Najjar, Raymond G.; Herrmann, Maria; Cintrón Del Valle, Sebastián M.; Friedman, Jaclyn R.; Friedrichs, Marjorie A.M.; Harris, Lora A.; Shadwick, Elizabeth H.; Stets, Edward G.; Woodland, Ryan J.
Abstract: Despite the important role of alkalinity in estuarine carbon cycling, the seasonal and decadal variability of alkalinity, particularly within multiple tidal tributaries of the same estuary, is poorly understood. Here we analyze more than 25, 000 alkalinity measurements, mostly from the 1980s and 1990s, in the major tidal tributaries of the Chesapeake Bay, a large, coastal‐plain estuary of eastern North America. The long‐term means of alkalinity in tidal‐fresh waters vary by a factor of 6 among seven tidal tributaries, reflecting the alkalinity of nontidal rivers draining to these estuaries. At 25 stations, mostly in the Potomac River Estuary, we find significant long‐term increasing trends that exceed the trends in the nontidal rivers upstream of those stations. Box model calculations in the Potomac River Estuary indicate that the main cause of the estuarine trends is a declining alkalinity sink. The magnitude of this sink is consistent with a simple model of calcification by the invasive bivalve Corbicula fluminea . More generally, in tidal tributaries fed by high‐alkalinity nontidal rivers, alkalinity is consumed, with sinks ranging from 8% to 27% of the upstream input. In contrast, tidal tributaries that are fed by low‐alkalinity nontidal rivers have sources of alkalinity amounting to 34% to 171% of the upstream input. For a single estuarine system, the Chesapeake Bay has diverse alkalinity dynamics and can thus serve as a laboratory for studying the numerous processes influencing alkalinity among the world's estuaries. Plain Language Summary: Alkalinity, which is the capacity of a water body to neutralize acid, is a useful quantity when studying the cycling of carbon in water bodies, including estuaries. Here we analyze alkalinity measurements in tidal tributaries of the Chesapeake Bay. Average alkalinity levels in the freshest parts of the estuaries varied by sixfold among seven tidal tributaries. Alkalinity was also found to increase over several decades at several locations, partially due to alkalinity increases in the rivers draining to Chesapeake Bay and also probably due to a reduction in the processes that remove alkalinity from estuarine waters. Evidence also supports the role of an invasive species, the Asiatic Clam, in the alkalinity removal in the Potomac River Estuary. More generally, we found evidence that tidal tributaries fed by high‐alkalinity rivers consumed alkalinity while tidal tributaries that are fed by low‐alkalinity rivers produce alkalinity. For a single estuarine system, the Chesapeake Bay has a wide range of alkalinity levels and a wide variety of processes that influence its alkalinity. Therefore, the Chesapeake Bay can serve as a laboratory for studying the alkalinity of many of the world's estuaries. Key Points: The long‐term means of alkalinity in fresh waters of the Chesapeake Bay vary by a factor of 6 among seven tidal tributaries Tidal tributaries fed by high‐alkalinity rivers have alkalinity sinks and those fed by low‐alkalinity rivers have alkalinity sources The alkalinity sink in the Potomac River Estuary declined from 1986 to 2013, leading alkalinity to increase in this system